2016
DOI: 10.3390/microorganisms4040044
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Lactic Fermentation of Gowé Using Lactobacillus Starter Culture

Abstract: A global model of the lactic fermentation step of gowé was developed by assembling blocks hosting models for bacterial growth, lactic acid production, and the drop of pH during fermentation. Commercial strains of Lactobacillus brevis and of Lactobacillus plantarum were used; their growth was modeled using Rosso’s primary model and the gamma concept as a secondary model. The optimum values of pH and temperature were 8.3 ± 0.3, 44.6 ± 1.2 °C and 8.3 ± 0.3, 3.2 ± 37.1 °C with μmax values of 1.8 ± 0.2 and 1.4 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…The maximum specific growth rate (μ m ) in the present investigation was lower than previously published values for other lactic acid bacteria except the specific growth rate obtained by Munanga, Loiseau, Grabulos, and Mestres (2016). Similarly, the maximum concentration of lactic acid which inhibits the production of lactic acid (P max ) was significantly higher than the value obtained by Monteagudo et al (1994).…”
Section: Comparison Of Parameter Valuescontrasting
confidence: 94%
“…The maximum specific growth rate (μ m ) in the present investigation was lower than previously published values for other lactic acid bacteria except the specific growth rate obtained by Munanga, Loiseau, Grabulos, and Mestres (2016). Similarly, the maximum concentration of lactic acid which inhibits the production of lactic acid (P max ) was significantly higher than the value obtained by Monteagudo et al (1994).…”
Section: Comparison Of Parameter Valuescontrasting
confidence: 94%
“…By re-inspecting Table 3, it can be noted that the modified logistic and logistic models should be rejected because some of their parameters have no statistical significance. It should be pointed out, however, that Munanga et al [40] studied the modeling of lactic fermentation of gowé and obtained a good fit of the logistic model to the experimental data of Lactobacillus brevis and L. plantarum growth during fermentation. The modified logistic model was also successfully used by Ilgin et al [16] to describe fermentative processes in the production of inulinase from carob extract using Aspergillus niger.…”
Section: Cell Growthmentioning
confidence: 99%
“…Lactobacillus is one of the most important LAB taxa present in fermented foods such as dairy, meats, and vegetable products (Yang et al, 2010;Yu et al, 2015). Owing to its resistance to low pH and ability to utilize a wide range of carbohydrate sources, Lactobacillus plantarum has been used as starter culture in various food fermentations such as a nondairy fermented beverage from a blend of cassava and rice (Freire et al, 2017), gowé (a fermented beverage made from malted and nonmalted sorghum flour; de J. C. Munanga et al, 2016), and fermented raw-dried meat sausages (Nedelcheva et al, 2010). It contributes significantly to the organoleptic properties, such as flavor and texture, of fermented foods (Bernardeau et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using lactose-negative Lactobacillus strains to control the post-fermentation acidification in yogurt (Chen et al, 2018), selection of acid-sensitive mutants, which are unable to continue fermentation below a certain pH, is another promising approach to improve control of post-fermentation acidification. F 0 F 1 -ATPase is a key enzyme in maintaining intracellular pH through extrusion of protons out of the cells by hydrolysis of ATP (Cotter and Hill, 2003). Several studies have reported that the basal activity of the F 0 F 1 -ATPase was lower in LAB strains that were more sensitive to low pH (Nannen and Hutkins, 1991;Yamamoto et al, 1996;Ongol et al, 2007).…”
Section: Introductionmentioning
confidence: 99%